The Influence of Diabetic Foot Exercise On Foot Sensitivity Of Diabetes Mellitus Patient Type 2 - I Gede Satria Astawa; Ni Luh Seri Astuti; Made Fridayanti; I Nyoman Dharma Wisnawa (Babali Nursing Research, 2023)
Introduction: Diabetes mellitus (DM), a chronic metabolic condition marked by elevated blood sugar levels (hyperglycemia), is brought on by an imbalance between the supply and demand for insulin. Decreased or missing insulin causes glucose to be retained in the circulation, increasing blood sugar levels while depleting the glucose that is required for cell survival and function. In type 2 DM patients, complaints of neuropathy are common.The aim of this study was to evaluate the impact of diabetic foot exercise on patients with Type 2 Diabetes Mellitus at the Selemadeg Timur II Health Center. Methods: Pre-experimental research is the type of study being conducted. During December 2022 to January 2023, the study was conducted at the Selemadeg Timur II Health Center. A total of 34 people were included in the sampling method with purposive sampling. The Wilcoxon Sign Rank test was used for analysis.Result: This study included 34 samples, and convenience or accidental sampling was used to choose the samples. The Wilcoxon test's asymp sign (2 tailed), which is 0.02 or 0.05, reveals the significance value. The results of the research show that before intervention the most sensitivity is moderate with 18 (61,2%) after treatment, data show that the most sensitivity is good with 16 (47%); p value 0,02<0,05. The sensitivity of the feet of Type II Diabetes Mellitus patients at the Selemadeg Timur II Health Center is influenced by diabetic foot exercise. Conclusion: Patients with Type II Diabetes Mellitus at the Selemadeg Timur II Health Center have sensitive feet, which is influenced by diabetic foot activity). It is important for families and communities to give motivation to the diabetes mellitus patients to do diabetic foot as one of alternative therapies to prevent foot complications such and increase foot sensitivity.Keywords: Diabetes Mellitus Type 2, Foot Sensitivity, and Diabetic Foot Exercise